2015
DOI: 10.4238/2015.october.29.7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of cultivated and wild tomatoes revealed by morphological traits and SSR markers

Abstract: ABSTRACT. In the current study, morphological traits and molecular markers were used to assess the genetic diversity of 29 cultivated tomatoes, 14 wild tomatoes and seven introgression lines. The three components of the principal component analysis (PCA) explained 78.54% of the total morphological variation in the 50 tomato genotypes assessed. Based on these morphological traits, a three-dimensional PCA plot separated the 50 genotypes into distinct groups, and a dendrogram divided them into six clusters. Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Zhou et al (2015a) evaluated a total of 29 cultivated tomatoes (S. lycopersicum), 14 wild tomatoes, and 7 introgression lines (ILs) developed from a cross between S. pennellii and S. lycopersicum with 9 morphological traits and 15 genomic-SSR and 13 EST-SSR primers. Zhou et al (2015b) compared the genomic simple sequence repeat (gSSR) and EST-derived SSR (EST-SSR) markers when analyzing genetic variability of 48 tomato cultivars from different countries.…”
mentioning
confidence: 99%
“…Zhou et al (2015a) evaluated a total of 29 cultivated tomatoes (S. lycopersicum), 14 wild tomatoes, and 7 introgression lines (ILs) developed from a cross between S. pennellii and S. lycopersicum with 9 morphological traits and 15 genomic-SSR and 13 EST-SSR primers. Zhou et al (2015b) compared the genomic simple sequence repeat (gSSR) and EST-derived SSR (EST-SSR) markers when analyzing genetic variability of 48 tomato cultivars from different countries.…”
mentioning
confidence: 99%
“…Shah et al, (2013), Benor et al, (2008) Zhou et al, (2015) and Korir et al, (2014) also reported similar results while studying the PIC of genomic SSRs and ESTT-SSR markers in various tomato lines. In the present study, SSR and RAPD markers detected medium locus polymorphism among the 24 tomato genotypes, indicating that both markers are of great utility for genetic diversity studies of tomatoes and can further be utilized in strengthening tomato breeding programmes.…”
Section: Resultsmentioning
confidence: 65%
“…Domestication of tomatoes by selecting preferred traits has led to low genetic diversity among cultivated tomatoes. A high similarity coefficient was found among 29 cultivated tomatoes using SSR markers, as published by Zhou et al, 2015. In 2011 three DNA markers to distinguish 26 tomato varieties, and found that nrDNA ITS region and rDNA 5S showed high nucleotide variation, whereas cpDNArbcL region was not suitable for tomato variety identification.…”
Section: Phylogenetic Analysismentioning
confidence: 74%